The legacy of deep ploughing and liming : A 1990s experimental site revisited - Hyväluoma, Jari; Keskinen, Riikka; Hetmanenko, Viktoriia; Kinnunen, Sami; Miettinen, Arttu; Niemi, Petri; Kaseva, Janne; Soinne, Helena (Elsevier, 2025)
Management of agricultural soils for increased productivity may exert positive or negative effects on soil structure, functions, and organic carbon (SOC) stocks. In this study, a field experiment established in 1993 on a clayey soil in southwest Finland was revisited to investigate the long-term effects of deep ploughing and liming on SOC concentration and stock, particulate (POC) and mineral-associated (MOC) fractions of SOC, pH, electrical conductivity (EC), bulk density (BD), porosity, critical pore size and cereal yield. The experiment comprised whole plots of conventional tillage (CT) to a maximum depth of ca. 20 cm, and plots deep ploughed to ca. 35 cm depth by a commercial (DP1) or by a self-made (DP2) plough. The tillage plots were divided into three split-plots assigned to liming treatments (low, medium and high). Three decades after implementation, the increasing liming rates still induced consistent differences in soil pH, a significant increasing effect on total porosity in the subsoil, and a marginally significant decrease in yield with an increase in soil acidity. The deep ploughing exerted a minor difference in topsoil texture, slightly lowered SOC concentration in the topsoil in DP2 in comparison to CT, and slightly higher subsoil SOC concentration in DP1 in comparison to CT, which indicated transfer of the topsoil SOC to deeper layers and dilution of the SOC in the new topsoil. However, no significant differences between the tillage treatments occurred in SOC stocks. In MOC and POC concentrations, there were no significant differences between the control and tillage treatments. The effects of deep ploughing on soil structural properties on the decadal time scale were minor and scattered. Cereal yield exhibited a slight negative trend for deep ploughing. For EC and BD, no treatment effects were recorded. Overall, the study showed that the legacy of soil management effects on soil properties can be persistent on decadal time scales, but no permanent structural damage due to deep ploughing nor gains in SOC stock accrual could be observed.
Keywords: tillage; stratification; carbon storage; pore system; yield